Idiopathic hemodynamically unstable polymicrobial purulent pericarditis: a rare case presentation. Issue 5 (23rd July 2020) - Ased, Suhaib; Payne, Andrew Nathan; Yang, Calvin
Abstract: Purulent pericarditis is an extremely rare disease accounting for <1% of pericarditis cases. Purulent pericarditis with hemodyamically unstable tamponade if untreated is fatal. Furthermore, although idiopathic polymicrobial disease is documented, a combination Haemophilus parainfluenzae, Prevotella buccae, and Citrobacter freundii have not been found in the literature by the authors. What follows is a case of a 58‐year‐old male who presented to the emergency department (ED) with these features and underwent emergent bedside pericardiocentesis and a brief review of current pericardiocentesis techniques in the emergency department.